Study OF Glycemic Index In Various Dates In Libya (Barnsali,Tabouni and Dagla) (مجلة العلوم الشاملة, 2024)
Three samples of date (Barnsali, Dagla and Tabouni) were taken from the local market in Al-Zawiya City at the period from ( 2020 / 11 / 1 )to ( 2021 / 2 / 7 ) to studying the effect of these types of dates on the glycemic index. Total sugar determinations for the three types of dates were carried out in industrial research center in Tajora, Tripoli, were as the following: 38.30% for Barnsali, 58.90% for Dagla and 45.30% for Tabouni. Then the effects of dates on blood sugar compared with standard glucose were done and the means where is the following: 65.00mg/100 ml for standard glucose, 73.07 mg/100 ml for Barnsali, 86.46 mg/100 ml for Dagla and 22.80 mg/100 for Tabouni. While, there were significant differences (p